OPTIMISASI MODEL PERSEDIAAN ECONOMIC PRODUCTION QUANTITY (EPQ) MULTI ITEM DENGAN KENDALA INVESTASI DAN KAPASITAS PENYIMPANAN PADA GUDANG PRODUK AKHIR - Sigit Susanto (Politeknik ATK Yogyakarta, 2016)
From the background of the company which produces several products ( ie bags, jackets , and shoes ) , limited capital or investment constraints , the limited storage capacity and the real system in the form of the production environment , obtained the formulation of the problem as follows: How to formulate a model of inventory in the production environment (model Economic Production Quantity / EPQ ) which is limited by the constraints of the investment and storage capacity constraints ? After the formulation of the model is obtained , followed by a search for solutions to the model were performed using lagrange multiplier that minimizes total inventory costs without exceeding storage capacity constraints and constrain to investment.